PENETRATING PANCREATICO-DUODENAL INJURIES: A 2-YEAR EXPERIENCE AT CMH PESHAWAR: Penetrating Pancreatico-Duodenal Injuries - Qasmi, Maj Shahzad Ahmed; Bashir, Riaz Anwar; Kiani, Faran; Yasin, Mohammad; Waqas, Ahmed (Pakistan Armed Forces Medical Journal, 2012)
Objective: To outline the various treatment options and outcomes in penetrating pancreatico-duodenal injuries with emphasis on the operative decision making strategies. Study Design: Descriptive study. Place and Duration of Study: Department of Surgery at Combined Military Hospital Peshawar, from 1st June 2008 to 30th May 2010. Patients and Methods: All combat casualties with penetrating pancreaticoduodenal injuries (PPDI) received in ‗Emergency reception‘ of Combined Military Hospital, Peshawar were included. Data was taken from the patients‘ medical charts and by personal evaluation and entered in a proforma. The variables used were age, sex, cause of the injury, haemo-dynamic status, conscious level, intensive care treatment duration, time to initial exploration, associated injury, grade of pancreatic injury according to Penetrating Abdominal Trauma Index (PATI) scoring system, grade of duodenal injury (according to PATI scoring system), total PATI score, operative repair, total hospital stay, morbidity, and mortality. Results: Twenty three patients having either or both of PPDI were included in the study out of 196 combat casualities. No case was excluded on basis of presence of associated injury. Mean age was 29.26 years (SD±6.489) with only one (4.3%) case of female gender, the rest were male patients or soldiers. Nineteen (82.6%) cases had primary mechanism/cause of injury being splinters from Improvised Explosive Devices (IEDs) or bomb blasts; while 4 (17.4%) cases had Gunshot Wounds. Eighteen (78.3%) patients were haemo-dynamically stable on arrival while 5 (21.7%) patients were unstable. Mean duration of stay in hospital was 10.6 days, with a range of 1-19 days (cases with high PATI score and un-stable haemodynamic status died with-in 24 hrs). Most cases of pancreatico-duodenal injury were of mild severity i.e. grade-1 or 2 and we encountered no case of grade-5 PPDI. Most commonly occurring associated injury was to small gut. Overall mortality was 6 (26.1%) out of 23 patients. "Pancreatico-duodenal mortality," or deaths attributable directly to duodenal or pancreatic injury or its management, occurred in only 1 patient. Other 5 died mainly due to associated injuries especially major vascular injury or head injury or due to increased contamination time in settings of colon or small gut injury. Conclusion: The majority of pancreatico-duodenal injuries can be managed by simple repair and efficient drainage along with consideration of damage control principles of surgery in haemodynamically-compromised patients.